Zinc oxide photocatalytic composite material taking porous carbon silicon as carrier as well as preparation method and application of zinc oxide photocatalytic composite material

Through the preparation of zinc oxide photocatalytic composite materials on the porous carbon carrier, the problem of insufficient zinc oxide catalytic performance in the existing technology has been solved, and the efficient degradation and chemical stability of organic dyes are improved.

CN119327494APending Publication Date: 2025-01-21YANCHENG INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411445245.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively degrade organic dyes with stable structures in treating wastewater, and the catalytic performance of bulk zinc oxide is insufficient, the degradation efficiency is poor or the degradation time is long.

Method used

Porous carbon silicon is used as a carrier, and zinc oxide photocatalytic composite materials are prepared through high-temperature nitrogen roasting or "one pot" method to improve the specific surface area and chemical stability of the catalyst.

Benefits of technology

Under the same amount of zinc oxide, composite catalytic materials have a better catalytic effect, can adsorb and degrade organic dyes more efficiently, and have higher chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327494A_ABST
    Figure CN119327494A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc oxide photocatalytic composite material taking porous carbon silicon as a carrier as well as a preparation method and application of the zinc oxide photocatalytic composite material. The photocatalytic composite material is prepared from the porous carbon silicon as the carrier and zinc oxide with active sites. Compared with a pure zinc oxide material, the zinc oxide can be attached to the surface of the carrier porous carbon-silicon material or coated inside the carrier porous carbon-silicon material, and meanwhile, the carrier porous carbon-silicon material provides rich pore tissues, so that coloring agent molecules can be effectively adsorbed and captured, and the coloring agent is more stable in performance. The contact probability and area of zinc oxide active sites and coloring agent molecules are increased, so that the zinc oxide can fully play a role in photocatalytic degradation of dye molecules; and under the condition of the same amount of zinc oxide, the porous carbon-silicon loaded zinc oxide has a stronger photocatalytic degradation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis, and specifically relates to a zinc oxide photocatalytic composite material with porous carbon silicon as a carrier, and a preparation method and application thereof. Background Art

[0002] Zinc oxide (ZnO) is an important inorganic functional material with excellent ultraviolet photocatalytic performance. The band gap of its bulk material at room temperature is ~3.3eV, corresponding to the wavelength of ultraviolet light between 350 and 400nm. Under the irradiation of ultraviolet light, nano ZnO can generate photogenerated electron-hole pairs, which is the main basis for its use as a photocatalyst. Photogenerated holes are a type of substance with strong oxidizing properties. They can react with water to generate hydroxyl (·OH) free radicals, and finally achieve the degradation of dyes in sewage through a series of oxidation processes.

[0003] Photocatalytic reactions mostly occur on the surface of the catalyst, so the specific surface area of ​​the photocatalyst will greatly affect the final catalytic performance of ZnO. At present, the methods for increasing the specific surface area of ​​nanomaterials can be mainly divided into two categories: one is to reduce the particle size of the material, and the other is to increase the porosity of the material, that is, to prepare the material into a porous material.

[0004] Dye wastewater accounts for a large proportion of industrial wastewater. Among them, water-soluble azo dyes are the main treatment targets of dye wastewater. Among the methods for treating printing and dyeing wastewater, the commonly used methods include oxidation, reverse osmosis, adsorption precipitation and neutralization. However, since the main structure of dye molecules in wastewater mostly contains benzene rings with relatively stable structures, it is difficult to achieve the desired effect using chemical and biological degradation methods. Different from traditional treatment methods, photocatalytic oxidation technology is a new type of modern water treatment technology. It can effectively destroy difficult-to-degrade pollutants with stable structures at the molecular scale. It has the advantages of high efficiency, low energy consumption, mild reaction conditions, wide application range and reduced secondary pollution. Therefore, exploring new, efficient and economically friendly photocatalytic oxidation active materials is of great significance for degrading organic dyes, treating dye wastewater and protecting the water environment. The existing technologies are mostly studied with crystalline porous materials as carriers, or changing the macroscopic morphology of the catalyst. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a zinc oxide photocatalytic composite material with porous carbon silicon as a carrier.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0009] The composite material uses porous carbon silicon as a carrier and zinc oxide as a catalytic active center;

[0010] Wherein, the content of zinc oxide accounts for 1-20wt% of the total mass.

[0011] As a preferred embodiment of the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier described in the present invention, the content of the zinc oxide accounts for 5-15wt% of the total mass.

[0012] As a preferred embodiment of the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier, the specific surface area of ​​the porous carbon silicon carrier is ≥ 200 m 2 / g.

[0013] As a preferred embodiment of the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier described in the present invention, the zinc oxide is prepared by high-temperature decomposition of zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, zinc citrate, a metal soluble zinc salt or a zinc-containing compound.

[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a zinc oxide photocatalytic composite material using porous carbon silicon as a carrier.

[0015] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0016] 2-Methylimidazole was dissolved in methanol, recorded as solution A, and zinc acetate was dissolved in deionized water, recorded as solution B;

[0017] Under stirring conditions, slowly add solution A to solution B, and after solution A is completely added; continue stirring for 48 hours; obtain a precipitated product; dry the precipitated product at 60-150° C. for 10-14 hours; obtain an imidazole zinc material;

[0018] CTAB is dissolved in deionized water, and ammonia water is added under vigorous stirring. After CTAB is evenly dissolved, imidazole zinc material is added and stirred for 4 to 5 hours; silicon source is added and stirred for 2 to 3 hours; heat preservation time is 24 to 25 hours; then centrifugation, washing and drying are performed;

[0019] The dried product is calcined in high temperature nitrogen at a temperature of 550-650° C. for 6-8 hours to obtain a porous carbon-silicon-supported zinc oxide photocatalytic composite material.

[0020] As a preferred embodiment of the method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier of the present invention, the preparation of the porous carbon silicon includes:

[0021] Organic matter or ammonium salt containing organic chain segments is dissolved in deionized water, and ethanol and ammonia water are added in sequence, accompanied by vigorous stirring; after CTAB is evenly dissolved, silicon source is added and stirred for 2 to 4 hours; the temperature is maintained for 24 to 26 hours; then centrifugation, washing and drying are performed;

[0022] The dried product is calcined in high temperature nitrogen at a temperature of 550-650° C. for 6-8 hours to obtain a porous carbon-silicon composite material.

[0023] As a preferred embodiment of the method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as the carrier described in the present invention, the organic matter includes triblock copolymers, polyethers, polyesters, polyethylene glycol, glucose or sucrose; the ammonium salt containing organic chain segments includes hexadecyltrimethylammonium bromide, hexadecyldiethylmethylammonium bromide, and hexadecyltrimethylammonium chloride.

[0024] As a preferred embodiment of the method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier according to the present invention, the silicon source includes organic silicon or inorganic silicon.

[0025] As a preferred embodiment of the method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier, the organic silicon includes tetraethyl orthosilicate, vinyl silicone oil or silicone resin; the inorganic silicon includes white carbon black, silicon dioxide, quartz sand, sodium silicate or silica sol.

[0026] As a preferred solution of the method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier according to the present invention, the composite material is used to degrade dyes in sewage.

[0027] Beneficial effects of the present invention:

[0028] 1. Porous carbon silicon-supported zinc oxide has higher chemical stability than zinc oxide particles; the composite catalyst prepared by core-shell pyrolysis has higher acid solution stability than other forms of materials.

[0029] 2. In view of the problems that bulk zinc oxide has poor efficiency or long degradation time in dye degradation in sewage, the present invention provides a method for preparing a zinc oxide photocatalyst with porous carbon silicon as a carrier. The composite photocatalytic material is obtained by high-temperature nitrogen roasting or a "one-pot" experimental method. Porous carbon silicon is used as a carrier to improve the adsorption and capture of organic dye molecules and increase the contact between the active sites of the catalyst and the organic dye molecules; at the same zinc oxide dosage, the composite catalytic material has a better catalytic effect; and the zinc oxide supported by porous carbon silicon has higher chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0031] Figure 1 This is the low-temperature nitrogen adsorption spectrum of the porous carbon silicon supported zinc oxide photocatalytic material in Example 1.

[0032] Figure 2 The schematic diagram is a structural diagram of a porous carbon silicon supported zinc oxide photocatalytic material prepared by the present invention; wherein a represents a mesoporous structure, and b represents a zinc oxide photocatalytic composite material with porous carbon silicon as a carrier.

[0033] Figure 3 This is the low temperature nitrogen adsorption spectrum of the zinc oxide material in Comparative Example 1.

[0034] Figure 4 It is the XRD spectra of the porous carbon silicon supported zinc oxide photocatalytic materials in Examples 1 to 8 of the present invention and the zinc oxide material in Comparative Example 1.

[0035] Figure 5 It is a graph showing the adsorption degradation removal rate of methylene blue by the porous carbon silicon supported zinc oxide photocatalytic material in Examples 1 to 8 and the zinc oxide material in Comparative Examples 1 to 5.

[0036] Figure 6 It is the residue after the porous carbon silicon supported zinc oxide photocatalytic material in Examples 1 to 8 and the zinc oxide material in Comparative Examples 1 to 5 are immersed in 0.05M HCl for different time periods. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0041] In the present invention, multiple parallel experiments were performed, and the experimental results were averaged, and "~" + numbers were used to represent the experimental results.

[0042] The material prepared in the embodiment of the present invention was subjected to a catalytic degradation test of methylene blue according to the following method:

[0043] Prepare 500mL of 2×10 -5 mol / L methylene blue solution was used as the reaction substrate, and a composite photocatalyst material based on 200mg zinc oxide was added. The mixture was stirred vigorously in the dark for 30 minutes to allow it to be fully mixed and reach adsorption-desorption equilibrium. 10mL was taken from the reaction mixture, and the volume was fixed to 100mL with deionized water. The supernatant was centrifuged at high speed to obtain the initial concentration C0. The visible light source was turned on to start timing. Samples were taken every 1h, 10mL of the reaction solution was taken and diluted to 100mL with deionized water. The supernatant was centrifuged to obtain the concentration C at the reaction time. t The reaction stopped after 6 hours. The absorbance value of the maximum absorption wavelength of methylene blue (λ = 664nm) was measured by UV-visible spectrophotometer. According to X% = [(C0-C t ) / C0]×100%, the degradation degree of methylene blue by the catalyst under ultraviolet light conditions can be obtained.

[0044] The material prepared in the embodiment of the present invention was tested for the acid-dissolved residual amount of methylene blue according to the following method:

[0045] In an ammonia buffer medium, with EDTA as the titrant, Cu-EDTA as the displacer, and a copper ion selective electrode as the indicator electrode, the zinc ion content in the zinc solution is titrated by potentiometric titration. Before the experiment, it is necessary to prepare EDTA standard titrant (0.02 mol / L), ammonia-ammonium chloride buffer solution with a pH of 10, and 0.05 mol / L Cu-EDTA solution (the amount of Cu and EDTA substance is 1:1).

[0046] Prepare 1L of 0.05mol / L hydrochloric acid solution as the dissolving solution, take 5 portions of 100ml of the dissolving solution, and add the photocatalyst materials of Example 1, Example 3, Example 4 and Example 5 with the same mass of zinc oxide (m0=0.200g) respectively; stir at room temperature, centrifuge every 10min, take 5mL of the supernatant and dilute to 100mL.

[0047] Take 2 ml of the diluted solution as the test solution, add 1.5 ml of pH = 10 buffer solution, 3 ml of 0.05 mol / L Cu-EDTA solution, and 60 ml of water, titrate to the endpoint on a T960 potentiometric titrator, and record the volume V of the EDTA standard titrant. t =0.200-[(0.02×V) / 2]×81.39×(100 / 5)×0.1, the remaining mass of zinc oxide in the solution at t min can be calculated.

[0048] The method for preparing the porous carbon silicon material in the embodiment of the present invention is as follows:

[0049] A. Preparation of porous carbon silicon carrier using CTAB as carbon source:

[0050] At room temperature, 0.96g CTAB, 98.4ml ammonia water, and 129.6ml deionized water were added to a 500ml two-necked flask in sequence, and the two flasks were sealed with frosted glass stoppers. The mixture was stirred magnetically for 30 minutes to obtain a uniformly mixed solution. Then, 6.0mL tetraethyl orthosilicate (TEOS) was added using a constant pressure separatory funnel and stirred magnetically for 4 hours. The mixture was then centrifuged at 6000rpm to obtain a white precipitate product, which was washed with deionized water several times and centrifuged and dried overnight at 60°C. The dried product was calcined at 500°C for 3 hours under nitrogen protection to obtain a porous carbon silicon carrier I. The calcined product was placed in a desiccator for storage.

[0051] B. Preparation of porous carbon silicon carrier using polyether as carbon source:

[0052] At room temperature, in a 500ml polypropylene bottle, add 6.0g of polyether (P123, average molecular weight ~5800) and 217.0ml of deionized water (H2O) in sequence, add 11.8g of concentrated hydrochloric acid (mass fraction 35%) during stirring, then add 6.0g of n-butanol, heat to 35°C in a water bath, keep stirring in a closed container for 1h, then add 12.9g of tetraethyl orthosilicate (TEOS); stir at 35°C for 24h; then transfer to a 100°C oven and let stand for 24h; after the reaction reaches the predetermined time, centrifuge and wash the centrifugal precipitate with deionized water several times, then place in an 80°C oven to dry overnight. The dried product was placed in a calcining furnace and calcined at 550°C under nitrogen protection to obtain a porous carbon silicon carrier. The two mouths of the flask were sealed with frosted glass stoppers and magnetically stirred for 30 minutes to obtain a uniformly mixed solution. Then, 6.0 ml of tetraethyl orthosilicate (TEOS) was added using a constant pressure separatory funnel and magnetically stirred for 4 hours. Then, the product was centrifuged at 6000 rpm to obtain a white precipitate product, which was washed with deionized water several times and centrifuged and dried overnight at 60°C. The dried product was calcined at 500°C under nitrogen protection for 3 hours to obtain a porous carbon silicon carrier II. The calcined product was placed in a desiccator for storage.

[0053] Example 1

[0054] Preparation of Porous Carbon-Silicon Supported ZnO Photocatalytic Composite Materials

[0055] Dissolve 5.488g zinc acetate dihydrate Zn(CH3COO)2·2H2O (0.025mol) in 100ml of 40℃ deionized water to prepare a 0.25mol / L zinc acetate solution; take 2.0g of porous carbon silicon carrier I, stir at 300rpm for 1h, and centrifuge to obtain a porous carbon silicon composite material loaded with zinc element; calcine the porous carbon silicon composite material loaded with zinc element in a nitrogen atmosphere at 300℃ for 6h; and obtain a catalytic material of porous carbon silicon loaded with zinc oxide. The mass of zinc element in the centrifugal supernatant is determined by titration precipitation method to be ~1.578g (calculated as zinc oxide); according to the zinc element content, the mass of zinc oxide loaded on 2.0g of porous carbon silicon is ~0.457g.

[0056] Figure 1 This is the low-temperature nitrogen adsorption spectrum of the porous carbon silicon-supported zinc oxide photocatalytic composite material of Example 1.

[0057] According to the test results, the overall specific surface area of ​​the material in this embodiment is 443.6 m 2 / g. When the relative pressure is high (P / P0>0.7), the adsorption curve and the desorption curve do not overlap, and there is a large hysteresis loop between the two, which indicates that the material in this embodiment has a mesoporous structure (such as Figure 2 shown).

[0058] Example 2

[0059] The difference between this embodiment and embodiment 1 is that the zinc source in the raw material is adjusted to 4.736 g zinc oxalate dihydrate Zn(COOCOO)2·2H2O (0.025 mol), and the rest of the preparation process is the same as that of embodiment 1, and a porous carbon silicon-supported zinc oxide photocatalytic composite material is obtained.

[0060] The mass of zinc element in the centrifugal supernatant was determined by titration precipitation method, which was ~1.597 g (calculated as zinc oxide); according to the zinc content, the mass of zinc oxide supported by 2.0 g of porous carbon silicon was ~0.438 g.

[0061] Example 3

[0062] The difference between this embodiment and embodiment 1 is that the zinc source in the raw material is adjusted to 3.408 g zinc chloride ZnCl2 (0.025 mol), and the rest of the preparation process is the same as that of embodiment 1, and a porous carbon silicon-supported zinc oxide photocatalytic composite material is obtained.

[0063] The mass of zinc element in the centrifugal supernatant was determined by titration precipitation method to be 1.607 g (calculated as zinc oxide); based on the zinc content, the mass of zinc oxide supported by 2.0 g of porous carbon silicon was 0.428 g.

[0064] Example 4

[0065] The difference between this embodiment and embodiment 1 is that the zinc source in the raw material is adjusted to 7.437 g zinc nitrate hexahydrate Zn(NO3)2·6H2O (0.025 mol), and the rest of the preparation process is the same as that of embodiment 1, and a porous carbon silicon-supported zinc oxide photocatalytic composite material is obtained.

[0066] The mass of zinc element in the centrifugal supernatant was determined by titration precipitation method, which was 1.635 g (calculated as zinc oxide). According to the zinc content, the mass of zinc oxide supported by 2.0 g of porous carbon silicon was 0.400 g.

[0067] Different from Example 1, the zinc sources in Examples 2 to 4 are zinc oxalate, zinc chloride, and zinc nitrate, respectively; when the same molar amount of zinc element is introduced, the mass of zinc oxide in Examples 2 to 4 is lower than that in Example 1 under the same calcination environment. The possible reason is that the solubility of zinc oxalate, zinc chloride, and zinc nitrate is higher than that of zinc acetate. During the centrifugation process, part of the zinc source will dissolve in the washing liquid, resulting in the loss of the zinc source, thereby reducing the quality of the oxidizing agent in the final calcined product.

[0068] Example 5

[0069] The difference between this embodiment and embodiment 1 is that the calcination temperature is adjusted to 400° C., and the rest of the preparation process is the same as that of embodiment 1, to obtain a porous carbon-silicon-loaded zinc oxide photocatalytic composite material.

[0070] The mass of zinc element in the centrifugal supernatant was determined by titration precipitation method, which was 1.579 g (calculated as zinc oxide). According to the zinc content, the mass of zinc oxide supported by 2.0 g of porous carbon silicon was 0.456 g.

[0071] Example 6

[0072] The difference between this embodiment and embodiment 1 is that the calcination temperature is adjusted to 500° C., and the rest of the preparation process is the same as that of embodiment 1, to obtain a porous carbon-silicon-supported zinc oxide photocatalytic composite material.

[0073] The mass of zinc in the centrifugal supernatant was determined by titration precipitation method, which was 1.576 g (calculated as zinc oxide). According to the zinc content, the mass of zinc oxide supported by 2.0 g of porous carbon silicon was 0.459 g.

[0074] Different from Example 1, the calcination temperature curves of Examples 5 and 6 are respectively raised to 400 and 500° C. in the program stage; the masses of zinc oxide in the final calcined products of Examples 5 and 6 are almost the same as those of Example 1, which indicates that calcination at 300° C. for 6 h can fully decompose zinc acetate into zinc oxide.

[0075] Example 7

[0076] The difference between this embodiment and embodiment 1 is that the porous carbon silicon carrier I in the raw material is adjusted to a porous carbon silicon carrier II, and the rest of the preparation process is the same as that of embodiment 1 to obtain a porous carbon silicon-loaded zinc oxide photocatalytic composite material.

[0077] The mass of zinc in the centrifugal supernatant was determined by titration precipitation method, which was 1.585 g (calculated as zinc oxide). According to the zinc content, the mass of zinc oxide supported by 2.0 g of porous carbon silicon was 0.450 g.

[0078] Different from Example 1, the porous carbon silicon material in Example 7 comes from Preparation Example 2 (using polyether as the carbon source); under the same calcination environment, the mass of zinc oxide in the calcined product is very similar to that in Example 1, and the degradation conversion rate is also very close.

[0079] Example 8

[0080] Preparation of porous carbon-silicon supported zinc oxide materials by thermal decomposition of core-shell structures

[0081] At room temperature, 16.221g of 2-methylimidazole (0.20mol) was dissolved in 100ml of methanol; it was recorded as solution A. 5.488g of Zn(CH3COO)2·2H2O (0.025mol) was dissolved in 100ml of deionized water; it was recorded as solution B. Under stirring conditions, solution A was slowly added to solution B. After solution A was completely added, stirring was continued for 48h; centrifuged at 4000rpm for 5min to obtain a precipitate product; the precipitate product was dried at 80℃ overnight; and imidazole zinc material was obtained. At 40℃, CTAB was dissolved in deionized water, and ammonia water was added under vigorous stirring. Keeping the temperature unchanged, after CTAB was evenly dissolved, imidazole zinc material was added, stirred for 4h; silicon source was added, stirred for 2h; the temperature was maintained for 24h; then centrifuged, washed and dried. The dried product was calcined at 550℃ for 6h in nitrogen to obtain a porous carbon silicon supported zinc oxide photocatalytic composite material.

[0082] The mass of zinc oxide in the photocatalytic composite material in this embodiment can be calculated by calcination and acid dissolution method; calcination can remove carbonaceous substances in the porous silicon-carbon carrier, and the acid dissolution method can dissolve zinc oxide. The content of zinc oxide in the composite material can be calculated based on the mass change, which is ~12%; that is, the mass of zinc oxide loaded on 2.0g of porous carbon silicon is ~0.273g.

[0083] Compared with Example 8, the materials in Examples 1 to 7 have a higher degradation conversion rate, mainly because the zinc oxide loading in Examples 1 to 7 is higher. At the same time, the material in Example 8 is prepared by thermal cracking of a core-shell structure, and the catalytic center is encapsulated inside the porous carbon silicon, and some catalytic centers cannot fully contact the adsorbate molecules; the degradation conversion rate of the materials in Examples 4 to 5 is slightly lower than that of the materials in other examples, because the catalytic center is slightly less than that in other examples.

[0084] Comparative Example 1

[0085] Preparation of zinc oxide materials

[0086] Weigh 5.488g of zinc acetate dihydrate Zn(CH3COO)2·2H2O and place it in a ceramic evaporating dish. Heat it with an alcohol lamp to decompose it into zinc oxide. During the heating process, stir the zinc acetate with a glass rod to heat it evenly and accelerate the decomposition. In order to ensure that zinc acetate is completely decomposed, the pyrolysis product is placed in a high-temperature furnace at 300℃ and air-roasted for 6h. The roasted product is placed in a desiccator for storage.

[0087] Figure 3 This is the low-temperature nitrogen adsorption spectrum of the zinc oxide material in Comparative Example 1.

[0088] According to the test results, the overall specific surface area of ​​the material in this embodiment is 5.235m 2 / g. When the relative pressure is high (P / P0>0.85), the adsorption curve and the desorption curve do not overlap, and there is a hysteresis loop between the two, which means that the material in this embodiment has a mesoporous structure. However, according to the preparation method of the zinc oxide material in Comparative Example 1, it is difficult for zinc oxide to have a porous structure; therefore, the mesoporous structure corresponding to the hysteresis loop in the adsorption-desorption curve comes from the accumulation between zinc oxide particles.

[0089] Figure 4 It is the XRD spectra of the porous carbon silicon supported zinc oxide photocatalytic composite materials in Examples 1 to 8 of the present invention and the zinc oxide material in Comparative Example 1.

[0090] According to the XRD spectrum, there is no impurity peak in Comparative Example 1, which is a pure zinc oxide phase; and the peak is sharp, indicating that it has a good crystalline morphology. Examples 1 to 8 have a broad peak in the diffraction angle range of 2θ = 15 to 30°, that is, amorphous carbon silicon materials. Compared with Comparative Example 1, there is a peak position of complete zinc oxide, indicating that zinc oxide particles exist in Examples 1 to 8, but the diffraction intensity is reduced, that is, the crystallinity of the zinc oxide loaded or coated by the porous carbon silicon is reduced.

[0091] Comparative Example 2

[0092] Weigh 5.488g of zinc acetate dihydrate Zn(CH3COO)2·2H2O and place it in a ceramic evaporating dish. Heat it with an alcohol lamp to decompose it into zinc oxide. During the heating process, stir the zinc acetate with a glass rod to make the zinc acetate evenly heated and accelerate the decomposition. Store the decomposition product in a desiccator for later use.

[0093] Comparative Example 3

[0094] The preparation process of zinc oxide is the same as that in Comparative Example 1, and the zinc source is 0.025 mol of zinc oxalate dihydrate Zn(COOCOO)2·2H2O (4.736 g).

[0095] Comparative Example 4

[0096] The preparation process of zinc oxide is the same as that in Comparative Example 1, and the zinc source is 0.025 mol of zinc chloride ZnCl2 (3.308 g).

[0097] Comparative Example 5

[0098] The preparation process of zinc oxide is the same as that in Comparative Example 1, and the zinc source is zinc nitrate hexahydrate Zn(NO3)2·6H2O (7.437 g).

[0099] Figure 5 It is a graph showing the adsorption degradation removal rate of methylene blue by the porous carbon silicon supported zinc oxide photocatalytic material in Examples 1 to 8 and the zinc oxide material in Comparative Examples 1 to 5.

[0100] According to the test results, it can be seen that the degradation conversion rates after 6 hours of illumination are 56.4%, 53.9%, 56.2%, 56.5%, and 56.5% in comparative examples 1 to 5, respectively, and 86.2%, 85.0%, 84.7%, 83.8%, 86.1%, 86.0%, 85.8%, and 72.3% in embodiments 1 to 8, respectively; compared with the material in comparative example 1, the catalytic materials in embodiments 1 to 8 (zinc oxide loaded in porous carbon silicon material or zinc oxide coated in porous carbon silicon material) have better effects on the degradation and conversion of methylene blue; the reason is that porous carbon silicon provides a large number of pore structures, which can adsorb and capture methylene blue molecules, thereby increasing the contact probability and contact area between the loaded zinc oxide and the methylene blue molecules, thereby improving the catalytic degradation effect.

[0101] Figure 6 It is the residue after the porous carbon silicon supported zinc oxide photocatalytic material in Examples 1 to 8 and the zinc oxide material in Comparative Example 1 are immersed in 0.05M HCl for different time periods.

[0102] According to the test results, when the immersion time is 60 min, the residual amounts of zinc oxide in the materials of Comparative Examples 1 to 5 are 0%, 0%, 0%, 0%, 0%, and 0%, respectively, and the residual amounts of zinc oxide in the materials of Examples 1 to 8 are 68.2%, 68.2%, 67.0%, 51%, 67.8%, 68.1%, 68.0%, and 70.0%, respectively; within the immersion time of 20 min, the zinc oxide in Comparative Examples 1 to 5 is quickly dissolved; as the immersion time increases to 40 min, in Comparative Example 2, due to the lack of high-temperature calcination decomposition (incomplete decomposition of zinc acetate), there is some undecomposed zinc acetate, so after immersion for 40 min, the zinc oxide in the materials of Comparative Examples 2 is not completely decomposed, and the zinc acetate in the materials of Examples 1 to 8 is not completely decomposed, and the zinc oxide ... , all dissolved; in Comparative Example 5, since zinc nitrate was not completely decomposed at 300°C, some zinc nitrate existed, and therefore, all dissolved after immersion for 40 minutes; there was a small amount of zinc oxide residue in Comparative Examples 1 and Comparative Examples 3-4; compared with the materials in Comparative Examples 1-5, the zinc oxide loaded in Examples 1-8 dissolved relatively slowly due to the protection of the porous carbon silicon carrier, and almost stopped dissolving after 40 minutes; compared with Examples 1-7, the zinc oxide in the material of Example 8 had a slightly larger amount of residue after immersion for 60 minutes. The reason was that the material of Example 8 was prepared by thermal cracking of a core-shell structure, and the catalytic center was coated inside the porous carbon silicon, which was not easily exposed to the solvent, and thus was retained to avoid being dissolved.

[0103] In view of the problems that bulk zinc oxide has poor efficiency or long degradation time in dye degradation in sewage, the present invention provides a method for preparing a zinc oxide photocatalyst with porous carbon silicon as a carrier. The composite photocatalytic material is obtained by high-temperature nitrogen roasting or a "one-pot" experimental method. Its innovation lies in: porous carbon silicon as a carrier can improve the adsorption and capture of organic dye molecules, increase the contact between the active sites of the catalyst and the organic dye molecules; under the same zinc oxide dosage, the composite catalytic material has a better catalytic effect; and the zinc oxide supported by porous carbon silicon has higher chemical stability.

[0104] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A zinc oxide photocatalytic composite material with porous carbon silicon as a carrier, characterized in that: The composite material uses porous carbon silicon as a carrier and zinc oxide as a catalytic active center; Wherein, the content of zinc oxide accounts for 1-20wt% of the total mass.

2. The zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 1, characterized in that: The content of zinc oxide accounts for 5-15wt% of the total mass.

3. The zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 1, characterized in that: The specific surface area of ​​the porous carbon silicon carrier is ≥200m 2 / g.

4. The zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 1, characterized in that: The zinc oxide is prepared by high-temperature decomposition of zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, zinc citrate, a metal soluble zinc salt or a zinc-containing compound.

5. The method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 1, characterized in that: include, 2-Methylimidazole was dissolved in methanol, recorded as solution A, and zinc acetate was dissolved in deionized water, recorded as solution B; Under stirring conditions, slowly add solution A to solution B, and after solution A is completely added; continue stirring for 48 hours; obtain a precipitated product; dry the precipitated product at 60-150° C. for 10-14 hours; obtain an imidazole zinc material; CTAB is dissolved in deionized water, and ammonia water is added under vigorous stirring. After CTAB is evenly dissolved, imidazole zinc material is added and stirred for 4 to 5 hours; silicon source is added and stirred for 2 to 3 hours; heat preservation time is 24 to 25 hours; then centrifugation, washing and drying are performed; The dried product is calcined in high temperature nitrogen at a temperature of 550-650° C. for 6-8 hours to obtain a porous carbon-silicon-supported zinc oxide photocatalytic composite material.

6. The method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 1, characterized in that: The preparation of the porous carbon silicon comprises: Organic matter or ammonium salt containing organic chain segments is dissolved in deionized water, and ethanol and ammonia water are added in sequence, accompanied by vigorous stirring; after CTAB is evenly dissolved, silicon source is added and stirred for 2 to 4 hours; the temperature is maintained for 24 to 26 hours; then centrifugation, washing and drying are performed; The dried product is calcined in high temperature nitrogen at a temperature of 550-650° C. for 6-8 hours to obtain a porous carbon-silicon composite material.

7. The method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier according to claim 6, characterized in that: The organic matter includes triblock copolymer, polyether, polyester, polyethylene glycol, glucose or sucrose; the ammonium salt containing organic chain segment includes hexadecyltrimethylammonium bromide, hexadecyldiethylmethylammonium bromide and hexadecyltrimethylammonium chloride.

8. The method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 6, characterized in that: The silicon source includes organic silicon or inorganic silicon.

9. The method for preparing the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 8, characterized in that: The organic silicon includes tetraethyl orthosilicate, vinyl silicone oil or silicone resin; the inorganic silicon includes white carbon black, silicon dioxide, quartz sand, sodium silicate or silica sol.

10. The use of the zinc oxide photocatalytic composite material with porous carbon silicon as a carrier as claimed in claim 6, characterized in that: The composite material is used for degrading dyes in sewage.

Citation Information

Cited By

  • Sulfur-doped zinc oxide nano material with broad-spectrum piezoelectric photocatalytic degradation characteristic as well as preparation method and application of sulfur-doped zinc oxide nano material

    CN121775869A